Mimicry of Central-Peripheral Immunity in Alzheimer's Disease and Discovery of Neurodegenerative Roles in Neutrophil - Park, Joseph; Baik, Sung Hoon; Mook-Jung, Inhee; Irimia, Daniel; Cho, Hansang (Frontiers in Immunology, 2019)
Neuroinflammatory roles of central innate immunity in brain parenchyma are well-regarded in the progression of neurodegenerative disorders including Alzheimer's disease (AD), however, the roles of peripheral immunity in central nervous system (CNS) diseases are less clear. Here, we created a microfluidic environment of human AD brains: microglial neuroinflammation induced by soluble amyloid-beta (Abeta), a signature molecule in AD and employed the environment to investigate the roles of neutrophils through the central-peripheral innate immunity crosstalk. We observed that soluble Abeta-activated human microglial cells produced chemoattractants for neutrophils including IL6, IL8, CCL2, CCL3/4, CCL5 and consequently induced reliable recruitment of human neutrophils. Particularly, we validated the discernable chemo-attractive roles of IL6, IL8, and CCL2 for neutrophils by interrupting the recruitment with neutralizing antibodies. Upon recruitment, microglia-neutrophils interaction results in the production of inflammatory mediators such as MIF and IL2, which are known to up-regulate neuroinflammation in AD. We envision that targeting the crosstalk between central-peripheral immune community is a potential strategy to reduce immunological burdens in other neuroinflammatory CNS diseases.